Short-term postharvest anoxia delays peel degreening and firmness loss through regulation of color- and cell wall–related genes in banana - Techavuthiporn, Chairat; Thammawong, Manasikan; Nakano, Kohei (My University, 2026)
Short-term anoxia (AnX) has emerged as a promising approach to extend postharvest quality of climacteric fruits, yet its mechanistic basis peel-associated ripening processes in banana remains unclear. This study examined the impact of 8 and 16 h AnX treatments on peel color, firmness, and the expression of essential genes related to fermentation, ethylene biosynthesis, pigment metabolism, and cell wall modification during ambient temperature storage. Visual and instrumental analyses showed that an 8 h AnX treatment effectively delayed peel degreening and firmness loss, whereas a 16 h treatment offered benefits but also induced stress-related transcriptional responses. Gene expression profiling revealed that AnX suppressed MaADH1 , while significantly upregulating MaADH2 immediately after treatment. A transient downregulation of the ethylene biosynthesis gene MaACO was accompanied by reduced expression of MaSGR and carotenoid-related genes ( MaPSY, MaPDS ), contributing to delayed color-transition. Firmness retention was associated with decreased expression of MaPG1 and MaXTH , whereas MaGLC was substantially upregulated only under prolonged anoxia. Heatmap analysis suggested that AnX disrupted the typical coordination between ethylene and downstream ripening-related genes, indicating altered associations among the analyzed genes. Overall, the findings demonstrate that moderate AnX (8 h) effectively delays ripening-related changes in banana peel through modulation of ethylene-dependent gene regulation, offering practical implications for sustainable postharvest management.
Keywords: Anoxic condition; Banana ripening; Fruit softening; Peel pigmentation; Postharvest gene expression